Dysphagia of aberrant right subclavian artery treated by endoscopic dilation: An alternative to surgical treatment in select cases—A case report. (2020) - Sadeghian, Homa; Moritz, Troy A.
Highlights: Aberrant right subclavian artery (ARSA) is a rare cause of dysphagia. Surgical intervention is the mainstem of therapy. Endoscopic dilation is a suitable treatment alternative in non-surgical candidates. Abstract: Introduction: The aberrant right subclavian artery (ARSA) is a rare cause of dysphagia. Surgical intervention has remained the mainstem of therapy, accompanied with certain morbidities and mortalities. Although rarely reported in literature, endoscopic dilation may be considered a suitable treatment alternative in patients who are not a surgical candidate or do not consent for surgery. We report a case suffering from dysphagia and diagnosed with ARSA treated by endoscopic dilation. Presentation of case: A 52-year-old male presented to our clinic in 2015 with dysphagia. Chest Computed Tomography scan confirmed the diagnosis of ARSA. He first underwent esophagogastroduodenoscopy (EGD) with staged dilation of the stricture, making him free of his symptoms for an approximate 2.5 years. Upon recurrence of symptoms in 2018, he underwent repeat endoscopic dilation, which again completely resolved the symptom with an excellent peri-operative and post-operative course. Conclusion: Endoscopic dilation of the esophageal stricture in patients with ARSA is a safe alternative to surgery in patients who are unable or unwilling to undergo surgery. It provides relief for a relatively long time and can be safely repeated multiple times upon recurrence.